Component sizing and energy management for a series hybrid electric tracked vehicle - Milićević, Stefan V.; Blagojević, Ivan A. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The paper presents a systematic approach to the development of a series hybrid electric tracked vehicle (HETV) including powertrain sizing and adequate energy management strategy (EMS) selection.Methods: Powertrain elements were sized considering key performance requirements. Three energy management strategies were proposed: Thermostat Control Strategy (TCS), Power Follower Control Strategy (PFCS), and Optimal Power Source Strategy (OPSS). The evaluation of the powertrain configuration and the three proposed EMSs was performed in the Simulink environment using a driving cycle containing significant acceleration, braking and steering. Results: The results showed that the OPSS proved to be the best due to increased fuel economy and a low battery state of charge (SOC) variation. Compared to the previous research of the same vehicle with a parallel hybrid configuration, significantly better results were achieved. The investigation of the results indicates that the proposed powertrain and control strategy offer 53.79% better fuel economy which indicates that the powertrain sizing was properly performed.Conclusions: The results of this work are of great importance for understanding the effect of proper powertrain sizing on fuel economy. Compared to the reference vehicle, the proposed configuration achieves significant improvement, most of which is attributed to adequate sizing. The OPSS proved to be the best strategy, thus confirming the theoretical hypothesis. The series hybrid configuration with the OPSS as the EMS proved to be a major candidate for use in HETVs.
Keywords: tracked vehicle; hybrid electric vehicle; energy management; control strategy; fuel economy